Polymer latex and polymer cement waterproof coating using same
By preparing polymer latex with high flexibility and strong cohesion, combined with an appropriate amount of emulsifier and initiator, the problem of reducing the cement hydration reaction rate of polymer cement waterproof coatings in low temperature environments is solved, and good under low temperature conditions is achieved Mechanical properties and waterproofing effects.
Patent Information
- Application Number
- CN202411244677.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-17
AI Technical Summary
The existing polymer cement waterproof coatings have reduced cement hydration reaction rate under low temperature environments, resulting in slow curing, poor mechanical strength and waterproofing effect, making it difficult to maintain good performance in low temperature environments in the north or winter.
By preparing polymer latex, using raw materials such as soft and hard monomers and long side chain acrylates, a high flexibility and cohesion interpenetrating cross-linking network structure is formed, and combined with an appropriate amount of emulsifier and initiator, the molecular weight of polymer latex and Crosslinking density ensures good mechanical properties when mixed with fillers such as cement under low temperature conditions.
It significantly improves the mechanical properties and flexibility of polymer cement waterproof coatings at low temperatures, ensuring that they can still maintain excellent waterproofing and mechanical properties in low temperature environments, and are suitable for different usage scenarios.
Smart Images

Figure BDA0005030921150000041 
Figure BDA0005030921150000051 
Figure BDA0005030921150000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer latex, and in particular relates to a polymer latex and a polymer cement waterproof coating using the same. Background Art
[0002] Polymer cement waterproof coating is a two-component waterproof coating composed of polymer latex, solvent, cement and other fillers. Its film-forming mechanism is as follows: after the components are mixed evenly, the cement in the system reacts with the aqueous solvent to form cement gel, and the polymer latex particles are fully diffused in the mixed slurry and adsorbed on the surface of cement, filler and cement hydration products; with the continuous consumption and volatilization of water, the particles aggregate and eventually entangle together to form a tight and continuous mesh membrane structure. Because polymer cement waterproof coating has the characteristics of both rigidity and flexibility, it has good weather resistance, flexibility and crack resistance. At the same time, due to its fast and convenient construction, high cost performance, environmental protection and non-toxicity, and wide range of applications, the market share of polymer cement waterproof coating is growing day by day.
[0003] However, since the hydration reaction rate of filler components such as cement is reduced at low temperatures, the strength of cement increases slowly, which will affect the curing of polymer cement waterproof coatings and the final mechanical strength of the coating. In addition, the film-forming rate of polymer emulsions will also be significantly reduced at low temperatures, the movement of emulsion molecules will slow down, and the drying rate will slow down, which is not conducive to the formation of a uniform and continuous waterproof film, resulting in a significant decrease in the strength and waterproof effect of the film after formation.
[0004] Therefore, it can be seen from the above that among the polymer cement waterproof coatings currently available in the market, few can still maintain good mechanical properties and low-temperature flexibility in low-temperature environments in the north or in winter. Summary of the invention
[0005] In order to improve the mechanical properties and flexibility of polymer cement waterproof coating in low temperature environment, the present invention provides a polymer latex and a polymer cement waterproof coating using the same.
[0006] According to one aspect of the present invention, a polymer latex is provided. Calculated by weight, raw materials for preparing the polymer latex include 400-600 parts of soft monomers, 200-250 parts of hard monomers, 5-10 parts of alkyl carboxylic acid monomers, 10-25 parts of amide monomers, and 10-20 parts of long side chain acrylates; wherein the glass transition temperature of the polymer latex is not higher than 240K; the soft monomer includes at least one of n-butyl acrylate and 2-ethylhexyl acrylate; the hard monomer includes at least one of styrene and methyl methacrylate; and the number of carbon atoms in the long side chain acrylate is not less than 11.
[0007] The present invention makes the glass transition temperature of the polymer latex not higher than 240K by matching appropriate soft and hard monomers, and at the same time introduces reactants rich in carboxyl and amide groups for modification polymerization, and increases the degree of entanglement and flexibility of the polymer latex by using long side chain acrylates with longer molecular side chain segments, thereby forming a network structure molecule with strong cohesive force and strong interpenetrating cross-linking. Thus, the molecular weight and cross-linking density of the polymer latex can be significantly improved, so that after the polymer latex provided by the present invention is mixed with fillers such as cement, good mechanical properties and flexibility can be achieved even under low temperature conditions.
[0008] Preferably, the soft monomer includes n-butyl acrylate, and the hard monomer includes styrene. Calculated by mass ratio, n-butyl acrylate:styrene=54-65:15-20.
[0009] Preferably, the long side chain acrylate has 12 to 18 carbon atoms.
[0010] Preferably, the long side chain acrylate includes at least one of isobornyl acrylate, lauryl acrylate, isodecyl acrylate, tetradecyl acrylate, and hexadecyl acrylate.
[0011] Preferably, the long side chain acrylate includes lauryl acrylate, and the mass content of lauryl acrylate in the long side chain acrylate is 60 to 100%.
[0012] Preferably, the amide monomer includes at least one of N-hydroxymethyl acrylamide, acrylamide and methacrylamide.
[0013] Preferably, the alkyl carboxylic acid monomer includes at least one of itaconic acid, maleic anhydride, maleic acid, methacrylic acid, acrylic acid, fumaric acid, and fumaric anhydride.
[0014] Preferably, the raw materials for preparing the polymer latex also include 10 to 15 parts of emulsifiers, calculated by weight, and the emulsifiers include anionic emulsifiers and nonionic emulsifiers, and the mass ratio of anionic emulsifiers to nonionic emulsifiers is 1 to 5: 1 to 2. In the polymer latex, the introduction of the emulsifier can reduce its surface tension, thereby improving the stability of the reaction system, thereby improving the compatibility of the polymer latex in the polymer cement waterproof coating. In addition, the type and compounding ratio of the emulsifier have an important influence on the reaction, which will affect the performance and molecular weight of the polymer.
[0015] Preferably, the anionic emulsifier includes at least one of sodium alkyl polyoxyethylene sulfonate, sodium dodecyl sulfonate, disodium salt of fatty alcohol polyoxyethylene ether sulfosuccinic acid half ester, and sodium alkyl diphenyl ether sulfonate; and / or, the nonionic emulsifier includes a fatty alcohol polyoxyethylene ether emulsifier.
[0016] Preferably, the anionic emulsifier includes sodium dodecyl sulfonate and sodium alkyl diphenyl ether sulfonate.
[0017] Preferably, the EO number of the fatty alcohol polyoxyethylene ether emulsifier is 10 to 40. The EO number of the fatty alcohol polyoxyethylene ether emulsifier refers to the difference in the polymerization degree (EO number) of the oxyethylene chain.
[0018] Preferably, the nonionic emulsifier includes 10EO fatty alcohol polyoxyethylene ether and 40EO fatty alcohol polyoxyethylene ether.
[0019] Preferably, the prepared polymer latex raw material further comprises a water-soluble initiator, and the water-soluble initiator comprises at least one of sodium persulfate, potassium persulfate and ammonium persulfate. The water-soluble initiator will affect the reaction rate of the polymer.
[0020] Preferably, the prepared polymer latex raw material further comprises a chain transfer agent, and the chain transfer agent comprises at least one of n-dodecyl mercaptan and tert-dodecyl mercaptan. The addition of the chain transfer agent can promote the cross-linking of molecular chains and the formation of a three-dimensional spatial network of the polymer.
[0021] Preferably, the prepared polymer latex raw material also includes a pH regulator including at least one of sodium hydroxide, potassium hydroxide and ammonia water.
[0022] Preferably, the prepared polymer latex raw material further includes a buffer salt, and the buffer salt includes at least one of sodium carbonate, sodium bicarbonate, ammonium bicarbonate, and sodium pyrophosphate.
[0023] Preferably, the prepared polymer latex raw material also includes a fungicide, and the fungicide includes at least one of isothiazolinone derivatives, benzimidazole esters, Dovihill-75, and 1,2-benzisothiazolin-3-one.
[0024] Preferably, the prepared polymer latex raw material also includes an aqueous solvent, and the aqueous solvent includes at least one of water, deionized water, ultrapure water, and ethanol.
[0025] Preferably, the method for preparing polymer latex comprises the following steps: S1. Preparing a pre-emulsion and a base liquid respectively, wherein the pre-emulsion comprises an emulsifier, a soft monomer, a hard monomer, and a long side chain acrylate; the base liquid comprises a seed emulsion, and the seed emulsion is obtained by polymerization of styrene monomer; S2. The base liquid is heated to 85-89°C, and then the first initiator is added, and then the pre-emulsion and the second initiator are dripped in for 4-5 hours, and then the temperature is kept for 0.5-2 hours; S3. The reaction system is cooled to 65-75°C, and then an oxidation-reduction initiator is introduced for post-treatment reaction for 0.5-2 hours, and the pH is adjusted to 7-8 after cooling to 50°C to obtain a polymer latex. The present invention can increase the molecular weight of the polymer latex by using a method of gradually dropping and polymerizing the seed emulsion at a variable speed, so that the cohesion of the latex particles is greatly improved. And by utilizing the various physical and chemical reactions that occur, a strong interpenetrating cross-linked network structure is formed, so that the density of the coating is greatly improved, thereby significantly improving the mechanical properties of the coating.
[0026] Another aspect of the present invention provides a polymer cement waterproof coating, which includes the polymer latex as described above. The polymer cement waterproof coating provided by the present invention can meet the requirements of different usage scenarios and at the same time ensure that it has high strength and elongation after long-term immersion in water or alkali.
[0027] Preferably, calculated by weight, the polymer cement waterproof coating includes 90 to 95 parts of polymer latex, 100 to 120 parts of filler, and 10 to 25 parts of aqueous solvent, wherein the filler includes cement. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0029] Example 1
[0030] Treatment Group 1A
[0031] This treatment group provides a polymer latex. The raw materials and proportions required for preparing the polymer latex are shown in Table 1. The monomers and additives used by this treatment group to prepare the polymer latex include the aqueous initiator, emulsifier, buffer salt, pH adjuster, chain transfer agent and bactericide mentioned in Table 1.
[0032] The seed solution mentioned in Table 1 is a seed emulsion obtained by polymerizing 100 wt % styrene monomer.
[0033] Table 1. Raw material composition for preparing polymer latex in treatment group 1A of Example 1
[0034]
[0035]
[0036] According to Table 1, the required raw materials were prepared in the following amounts, and the polymer latex was prepared according to the following steps.
[0037] The preparation steps are as follows:
[0038] S1. Preparation of pre-emulsion: add emulsifier and 43% deionized water (43%*450 parts by mass, the same below) to the emulsifier, disperse for 15 minutes, add soft monomer, hard monomer, alkyl carboxylic acid monomer, amide monomer, long side chain acrylate and stir for 15 minutes to obtain pre-emulsion; Preparation of reactor bottom liquid: add 50% deionized water and seed latex to the reactor, and heat to the temperature in the reactor to reach 85-89°C;
[0039] S2. The water-soluble initiator is divided into two parts, wherein the first part of the water-soluble initiator: the second part of the water-soluble initiator is calculated by mass ratio, 2:3; the first initiator is dissolved in 2% deionized water, and the second initiator is dissolved in 5% deionized water; the base liquid is heated to 85-89°C, and then the first initiator is added, and then the pre-emulsion and the second initiator are dripped, the dripping time is 4.5 hours, and then kept warm for 1 hour;
[0040] S3. After the heat preservation is completed, the temperature is lowered to 75°C, and then post-treated with tert-butyl hydroperoxide-vitamin C for 45 minutes. After the post-treatment, the temperature is lowered to 50°C, the pH is adjusted to 7.5 with 5% sodium hydroxide, and then an isothiazolinone derivative is added. The material is filtered to obtain a polymer latex.
[0041] According to Table 2, the required raw materials are prepared in the required amounts, and the polymer cement waterproof coating is prepared according to the following steps. Specifically, the preparation steps are as follows: According to Table 2, the required raw materials are prepared in the required amounts, the raw materials required for the formula are mixed, and then the raw material mixture is stirred by a disperser at a stirring speed of 400-800r / min for 5 minutes. After the raw materials are fully mixed, the polymer cement waterproof coating can be obtained.
[0042] Table 2. Formula composition of polymer cement waterproof coating
[0043] Material Name Weight parts / parts JS with LaTeX 90-95 water 7-15 Defoaming agent 0.5-1 Thickener 0.5-1 cement 40-50 Sand 5-10 Heavy Calcium 30-45
[0044] The treatment group 2A and the comparative groups 1A to 3A of Example 1 prepared polymer latex and polymer cement waterproof coatings with reference to the formula and method provided by the treatment group 1A of Example 1, with the mass ratio of n-butyl acrylate and styrene used in the polymer latex formula as a variable (keeping the total mass fraction of n-butyl acrylate and styrene unchanged), and the variables used to prepare polymer latex in the treatment groups 1A to 2A and the comparative groups 1A to 3A of Example 1 are shown in Table 3. In addition to the above differences, the operation steps for preparing polymer latex and polymer cement waterproof coatings in the treatment groups 2A and the comparative groups 1A to 3A of Example 1 are strictly consistent with those in the treatment group 1A of Example 1. Among them, T g Represents the glass transition temperature of polymer latex.
[0045] Table 3. Variables of each treatment group in Example 1
[0046] Group Monomer ratio <![CDATA[T g / K]]> Treatment Group 1A n-Butyl acrylate: styrene = 60:17 239 Treatment Group 2A n-Butyl acrylate: styrene = 62:15 236 Comparative Group 1A n-Butyl acrylate: styrene = 54:23 245 Comparative Group 2A n-Butyl acrylate: styrene = 56:21 246 Comparative group 3A n-Butyl acrylate: styrene = 58:19 243
[0047] Comparative group 4A
[0048] This comparative group prepared polymer latex and polymer cement waterproof coatings by the formula and method provided by treatment group 1A of reference example 1. The difference from treatment group 1A is that this comparative group replaced n-butyl acrylate with n-propyl acrylate in equal parts by mass. Except for the above differences, the operation steps for preparing polymer latex and polymer cement waterproof coatings in this comparative group were strictly consistent with those of treatment group 1A of example 1.
[0049] Comparative group 5A
[0050] This comparative group prepared polymer latex and polymer cement waterproof coatings by the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A is that tert-butyl methacrylate was used to replace styrene in equal parts by mass in this comparative group. In addition to the above differences, the operation steps for preparing polymer latex and polymer cement waterproof coatings in this comparative group were strictly consistent with those of treatment group 1A of Example 1.
[0051] Test Example 1
[0052] 1. Test subjects
[0053] The polymer latex prepared in each treatment group and comparison group of Example 1 and the polymer cement waterproof coating using the latex.
[0054] 2. Test Method
[0055] The performance of the test objects was tested in accordance with the industry standard GB / T23445-2009 "Polymer Cement Waterproof Coating". The test items and their corresponding technical indicators are shown in Table 4.
[0056] Table 4. Test items and their corresponding technical indicators
[0057]
[0058] 3. Test results and analysis
[0059] The test results of this test example are shown in Table 5-1 and Table 5-2.
[0060] It can be seen from the data of treatment groups 1A to 2A of Example 1 and comparison groups 1A to 3A that when the glass transition temperature (T g ) is higher than 240K, although it has excellent bonding strength before and after immersion in water and alkali, and the elongation is higher than that of the competing products, it still cracks at -20°C like the competing products. Therefore, combined with the comparison group 3A and the comparison group 4A, the above experiments show that the present invention can make the polymer latex maintain good low-temperature flexibility and good mechanical properties at -20°C through appropriate formulation and regulation of the glass transition temperature of the polymer latex.
[0061] Table 5-1. Test results of test case 1
[0062]
[0063]
[0064] Table 5-2. Test results of test case 1
[0065]
[0066] Example 2
[0067] Treatment group 1B in Example 2 prepared polymer latex and polymer cement waterproof coating using the same according to the formula and method provided by treatment group 1A in Example 1. Treatment groups 2B to 4B in Example 2 prepared polymer latex and polymer cement waterproof coating using the same with reference to the formula and method provided by treatment group 1B in Example 2, with the material of long side chain acrylate (total mass fraction of 18) used in the polymer latex formula as a variable. The variables used in Example 2 to prepare polymer latex are shown in Table 6. Except for the above differences, the operation steps for preparing polymer latex and polymer cement waterproof coating using the same in Example 2 are strictly consistent with those in Example 1.
[0068] Table 6. Formula composition of polymer cement waterproof coating
[0069]
[0070]
[0071] Comparative group 1B
[0072] This comparative group prepared polymer latex and polymer cement waterproof coatings by the formula and method provided by treatment group 1A of reference example 1. The difference from treatment group 1A is that this comparative group replaced lauryl acrylate with 2-ethylhexyl methacrylate monomer in equal parts by mass. Except for the above differences, the operation steps for preparing polymer latex and polymer cement waterproof coatings in this comparative group were strictly consistent with those of treatment group 1A of example 1.
[0073] Test Example 2
[0074] 1. Test subjects
[0075] The polymer latex prepared in each treatment group and comparison group of Example 2 and the polymer cement waterproof coating using the latex.
[0076] 2. Test Method
[0077] Refer to the method provided in Test Example 1.
[0078] 3. Test results and analysis
[0079] The test results of this test case are shown in Table 7.
[0080] It can be seen from the data in Table 7 that by matching different long side chain acrylates, it is possible to ensure that the polymer latex has good flexibility in a low temperature environment while enhancing its mechanical properties in a normal environment. This may be because the long side chain acrylate can increase the degree of entanglement and flexibility of the polymer latex through its longer molecular side chain segments, thereby forming a network structure molecule with strong cohesive force and strong interpenetrating cross-linking. This can significantly increase the molecular weight and cross-linking density of the polymer latex, so that after the polymer latex provided by the present invention is mixed with fillers such as cement, while ensuring low temperature flexibility, it can also effectively enhance the cohesive force of the coating to make its mechanical properties more excellent.
[0081] Table 7. Test results of test case 2
[0082]
[0083]
[0084] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polymer latex, It is characterized in that Calculated by weight, the raw materials for preparing the polymer latex include 400-700 parts of soft monomers, 100-250 parts of hard monomers, 5-10 parts of alkyl carboxylic acid monomers, 10-25 parts of amide monomers, and 10-20 parts of long side chain acrylates; Wherein, the glass transition temperature of the polymer latex is not higher than 240K; The soft monomer includes at least one of n-butyl acrylate and 2-ethylhexyl acrylate; The hard monomer includes at least one of styrene and methyl methacrylate; The carbon number of the long side chain acrylate hydrophobic segment is not less than 11.
2. The polymer latex according to claim 1, It is characterized in that The soft monomer includes the n-butyl acrylate, and the hard monomer includes the styrene. Calculated by mass ratio, the n-butyl acrylate: the styrene = 54-65: 15-23.
3. The polymer latex according to claim 1, It is characterized in that The carbon number of the long side chain acrylate is 12-18.
4. The polymer latex according to claim 3, It is characterized in that The long side chain acrylate includes at least one of isobornyl acrylate, lauryl acrylate, isodecyl acrylate, tetradecyl acrylate and hexadecyl acrylate.
5. The polymer latex according to claim 4, It is characterized in that The long side chain acrylate includes lauryl acrylate, and the mass content of lauryl acrylate in the long side chain acrylate is 60 to 100%.
6. The polymer latex according to claim 1, It is characterized in that The amide monomer includes at least one of N-hydroxymethyl acrylamide, acrylamide and methacrylamide.
7. The polymer latex according to claim 1, It is characterized in that The alkyl carboxylic acid monomer includes at least one of itaconic acid, maleic anhydride, maleic acid, methacrylic acid, acrylic acid, fumaric acid, and fumaric anhydride.
8. The polymer latex according to any one of claims 1 to 7, It is characterized in that The method for preparing the polymer latex comprises the following steps: S1. preparing a pre-emulsion and a base liquid respectively, wherein the pre-emulsion comprises an emulsifier, the soft monomer, the hard monomer, and the long side chain acrylate; the base liquid comprises a seed emulsion, and the seed emulsion is obtained by polymerizing a styrene monomer; S2. The base liquid is heated to 85 to 89°C, and then the first initiator is added, and then the pre-emulsion and the second initiator are dripped in for 4 to 5 hours, followed by insulation for 0.5 to 2 hours; S3. The reaction system is cooled to 65-75° C., and then an oxidation-reduction initiator is introduced for post-treatment reaction for 0.5-1 hour. After cooling to 50° C., the pH is adjusted to 7-8 to obtain the polymer latex.
9. A polymer cement waterproof coating, It is characterized in that The polymer cement waterproof coating comprises the polymer latex as claimed in any one of claims 1 to 8.
10. The polymer cement waterproof coating as claimed in claim 9, It is characterized in that Calculated by weight, the polymer cement waterproof coating includes 90 to 95 parts of the polymer latex, 100 to 120 parts of filler, and 10 to 25 parts of aqueous solvent, wherein the filler includes cement.
